PREDIKSI PERBAIKAN LAYANAN MENGGUNAKAN METODE ANALISIS BERTAHAN (SURVIVAL ANALYSIS) (STUDI KASUS PT. MITRA NASIONAL KUALITAS JAKARTA) - Taufik Djatna, Hartrisari Hardjomidjojo dan Tanti Meylani (E-Jurnal Agro-Industri Indonesia) (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT Keeping customer satisfaction is important to keep customer loyalty which can be done by implementing Customer Relationship Management (CRM). CRM has main objective to increase customer retention through increase customer satisfaction. Giving the appropriate service can gain customer satisfaction. The appropriate service given based on customer’s assesment on service variabel importance rate. In addition, service evaluation was done by implementing survival analysis method, to got information about the decline of customer satisfaction based on customer retention. The objectives of this research were to assess service variables important to customer. Then, prediction was needed to build a service recovery based on survival analysis component which were retention curve, hazard curve dan survival curve. The research in Mitra Nasional Kualitas, Ltd Jakarta, resulted in customer assess on reliability and assuranceattributes from service variable wasvery important. The decline of retention rate and survival rate and also the incline of hazard rate indicate that the firm need to do service recovery.   Keywords: Customer Relationship Management, Survival Analysis, Service Variable